Communicative Approach in Teaching A Foreign Language - Luqmonovna, Odinayeva Nilufar; Nozima, Norkulova (Innovative Technologica: Methodical Research Journal, 2024)
This article examines the communicative approach in foreign language teaching, exploring its theoretical foundations, methodological principles, and practical applications. Through a comprehensive literature review, including both international and Uzbek sources, the study analyzes the evolution of the communicative approach, its impact on language acquisition, and its effectiveness in developing learners' communicative competence.